Hubungan Jumlah Tusukan Spinal Anestesi Lebih dari Satu Kali dengan Kejadian Post-Dural Puncture Headache pada Pasien Sectio Caesarea di RSUD Ajibarang - Aris Ahmat; Magenda Bisma Yudha; Wasis Eko Kurniawan; Made Suandika (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Background: Spinal anesthesia is a commonly used technique for cesarean section procedures. However, this technique carries a risk of complications, one of which is post-dural puncture headache (PDPH). PDPH can be caused by several factors, including multiple attempts at spinal needle insertion. Objective: To determine the relationship between the number of spinal anesthesia punctures greater than once and the incidence of PDPH in cesarean section patients at RSUD Ajibarang. Methods: This study used a quantitative design with a cross-sectional approach. A total of 80 cesarean section patients who underwent spinal anesthesia were selected using purposive sampling. Data were collected through observation and interviews and analyzed using the Spearman correlation test. Results: A total of 96.3% of patients experienced two punctures, while 3.8% experienced three punctures. Most patients did not experience PDPH (90.0%), while 8.8% reported moderate headache and 1.3% reported severe headache. The analysis showed a significant relationship between the number of spinal punctures and the incidence of PDPH (p=0.001; r=0.367). Conclusion: There is a significant correlation between the number of spinal anesthesia attempts and the incidence of PDPH among cesarean section patients at RSUD Ajibarang. The greater the number of spinal punctures, the higher the risk of developing PDPH.